Participatory training program on HIV/AIDS among anganwadi workers for training adolescent girls: an experience from a rural area of Karaikal, Puducherry, India - Sundaram, Ramkumar; Srinivasan, Vijayalakshmi (International Journal Of Community Medicine And Public Health, 2020)
Background: Recently HIV epidemic in India was gradually escalating to low risk groups like adolescents. Focusing on adolescent empowerment is the strategy for obtaining their adherence to prevention of HIV/AIDS. Though anganwadi workers (AWWs) play a critical role in creating awareness on behaviour change in the community; also, they need an excellent knowledge on HIV/AIDS before creating awareness to the community. So, this study aimed to assess the knowledge on HIV/AIDS among adolescent girls and AWWs and also to determine the effectiveness of Participatory Training Program to AWWs in bringing improvements in the knowledge among adolescent girls. Methods: Present quasi-experimental study was conducted among adolescent girls ages 15 to 18 years at Serumavilangai Village, Karaikal, Puducherry during June-September 2018. AWWs from the selected village were included for participatory training program. Results: Total 86 adolescents participated the survey. Awareness regarding HIV/AIDS was only 40% before intervention. FGD among AWWs showed poor knowledge on HIV/AIDS. During intervention, AWWs were used as a medium for giving interventions, it was observed that there was a wide difference in their knowledge of adolescent girls before and after intervention (81.4%) on HIV/AIDS with statistical significance (0.03). Conclusions: Before intervention awareness on HIV/AIDS were lacking in both adolescent girls and AWWs. This shows a difficulty in accessing health information in rural India. Therefore, providing periodic training programme to AWWs as peer health educators for disseminating information on HIV/AIDS may bridge the gap by proving valid information’s to high risk groups in the community.